The Root and Nothing but the Root: Primary Compounds in Dutch. (10th April 2017) - De Belder, Marijke
Abstract: This article is an addendum to recent contributions on the structure of compounds in root‐based frameworks, such as the Exoskeletal Model (Borer2009, 2013a :chap. 6, 2013b) or Distributed Morphology (Harley2009 ). It presents a subtype of Dutch primary compounds of which the nonhead is demonstrably a bare root. The nonhead of this type of compounding is fully acategorial. It does not contain categorial heads (i.e., little heads) and neither is it categorized otherwise. As such, the discussion substantiates the root hypothesis (Halle & Marantz1993 ; Borer2005a, b, 2013a ) and supports the view that the root does not need to be licensed by superstructure in order to be interpretable or realizable (see Alexiadou & Lohndal2013, pace Arad2003, Marantz2008, Ramchand2008, Starke2009 ).